Preliminary study of the lime oil - Lim, Kong Yan; Castillo, Amorita (Quezon City: College of Pharmacy, University of the Philippines, 1978.)
The fresh peel of Citrus aurantifolia (Christm) Swingle yielded approximately from 1.80 to 1.88% essential oil. Moisture content of the peel was 67.5%. The oil gave the following physical properties: specific gravity at 25° 0.8598, refractive index at 20° 1.4725 and optical rotation at 20° +42°. The oil was soluble in 95% ethanol and an equal volume of most organic solvents. Thin layer chromatography and ultraviolet spectrophotometry showed the presence of limone
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, 1978.
Keywords: Lime o